Effects of different levels of sugar beet roots based concentrates on the performance of Tagger male kids - M. E, Elimam; Elshafie, N. O. H; Eltayeb, B. A.; Elamin, K. M. Elamin (Gezira Journal of Agricultural Science; Vol 15 No 2 (2017), 2017)
High meat demand in the Sudan enhanced improvement of goat meat production. Tagger is a promising meat breed due to good conformation and high meat quality. Nutrition is a main constraint for goat meat production. Sugar beet is introduced into the Gezira State with no information on effects of dried sugar beet roots (DSBR) based concentrates level on Tagger kids performance, carcass characteristics and meat composition. Twelve Tagger males of 6 months old were housed in individual pens, divided into 3 groups, each with 4 animals and allocated at random to the experimental diets. They were weighed weekly for 8 weeks with a two weeks preliminary period. They were fed groundnut haulm (GNH) ad lib . in two equal meals at 8.0 am and 4.0 pm and refusals were collected and weighed daily. The animals were fed different levels of DSBR based concentrates: 0 (control), 150g and 300g, in two equal parts before GNH meals. The concentrates contained 68% DSBR,15% groundnut cakes, 15% sunflower cakes, 1% salt and 1% oyster shell. Samples of feeds and refusals were stored for laboratory analysis.  Resultd showed that groundnut haulm ( 30% CP, 8.8% CF, 4.8% ash and 48.2% NFE) had better proximate analysis than refusals which generally improved with concentrates levels. Dried sugar beet had 12.9% CP, 11.0% CF and 59.25% NFE and the concentrates had 42.25% CP, 2.0% CF and 49.5% NFE. Overall mean BW generally increased with concentrates level (10.78, 10.9 and 12.19kg at 0, 150 and 300g, respectively), but  not significantly different. Overall mean daily feed intakes varied with concentrates level and were 1550.89, 1187.46 and 1545.67g at 0, 150 and 300g concentrates, respectively, and were significantly least in animals fed 150g concentrates. Weekly weight gain generally increased with concentrates level in all weeks and was highest in animals fed 150g concentrates with no significant effects for concentrates level. It was 0.55, 0.68 and 0.60 kg at 0, 150 and 300g concentrates, respectively. It is recommended to use DSBR based concentrates in fattening Tagger kids.     حفز ارتفاع الطلب  على اللحوم وأسعارها في السودان تحسين لحوم الماعز. تعتبر التقر سلالة واعدة لإنتاج اللحوم لجودة القوام ونوعية اللحم.  إلا أن التغذية من المعوقات الرئيسة لإنتاج لحوم الماعز.  أدخل بنجر السكر لولاية الجزيرة ولا تتوفر معلومات عن أثر مستوى جذر البنجر الجاف) ج ب ج (على أداء جديان التقر وصفات الذبيحة  وتركيب اللحم.  وضعت 12 من ذكور جديان التقر بعمر 6 أشهر في حظائر فردية  وقسمت الى 3 مجموعات بكل منها 4 حيوانات  ووزعت عشوائيا على أعلاف الدراسة. وزنت الحيوانات أسبوعيا لمدة 8 أسابيع منها أسبوعين فترة إعدادية. أعلفت الحيوانات تبن الفول السوداني )ت ف س) حسب الرغبة في وجبتين متساويتين عند الثامنة صباحا والرابعة مساء وجمع ووزن العلف المتبقي.  كما أعلفت الحيوانات مستويات مختلفة من عليقة مركزة ترتكز على )ج ب ج  (عند صفر( الشاهد), 150 و300جم في جزئين متساويين  قبل وجبتي ت ف س. احتوت العليقة المركزة على 68% ج ب ج و15%  امباز فول سوداني و15%  تبن زهرة الشمس و1% ملح و 1% صدف  حفظت عينات من  الأعلاف والعلف المتبقي للتحليل المعملي.  حُللت المعلومات إحصائيا باستخدام تحليل التباين واستخدم اختبار دنكن لفصل اختلافات المتوسطات. كان  ت ف س (  30% بروتين خام ، 8.85 ألياف خام، 4.8% رماد و 48.2% جزء خالي من النتروجين) أحسن في التحليل التقريبي من المتبق.والذي تحسنت نوعيته بارتفاع مستوى العليقة المركزة. كان تركيب  ج ب ج 12.95 % بروتين خام ، 11% الياف خام و 59.25% جزء خالي من النتروجين .وتركيب العليقة المركزة  42.25 % بروتين خام ، 2% ألياف خام و 49.5% جزء خالي من النتروجين .  زاد متوسط الوزن الكلى مع زيادة العليقة المركزة (10.78 ،  10.9 و 12.19عند صفر و 150 و 300 جم عليقة مركزة على التوالي بدون فروقات معنوية . (P>.05)  تباين متوسط المتناول من العلف تبعاً لمستوي المركزات وكان 1550.89 و 1187.46 و 1545.67 جم عند صفر و 150 و300 جم عليقة مركزة ، علي التوالي وكان أقل معنوياً للحيوانات التي غُذيت علي  150عليقة مركزة.  تباينت زيادة الوزن الأسبوعي بزيادة مستوي العليقة المركزة في كل الأسابيع وكانت الأعلى للحيوانات عند 150 جم بدون زيادة معنوية. وكانت 0.55 و0.68 و 0.60 كجم عند صفر و 150 و300 جم عليقة مركزة، علي التوالي. يوصي باستخدام علائق جذور بنجر السكر المجففة لتسمين جديان التقر.